Effectiveness Of Semi-Transparent Photovoltaic Application At Highrise Vertical Facade In Malaysian Urban Area - Rababah, Haitham Esam Mahmoud (2024)
This research endeavours to leverage the vertical facades of buildings within Malaysia's high-rise urban areas to generate renewable energy, addressing the challenge of limited space for traditional solar installations. Specifically focusing on the urban setting of Kuala Lumpur, the study employs sophisticated modelling and simulation techniques to assess solar exposure potential and optimise the placement of photovoltaic (PV) panels. The primary objective is to explore the feasibility and effectiveness of utilising vertical surfaces for solar energy production, by concentrating on a specific area encompassing high-rise buildings in Kuala Lumpur. By using Revit software for developing a conceptual 3D model and IES VE software for simulations, the study focused on factors such as neighbouring buildings, shading effects, and distances to ascertain their impact on solar exposure. The findings highlighted that installing PV panels have the potential to reduce electricity costs by 42.67%. Moreover, the research underscores the economic viability of this approach, with an estimation that PV panels have an average Return on Investment (ROI) between 6.7% and 11%, depending on the ratio of PV panels to windows, this innovative integration promises significant returns for building owners. Overall, the research signifies a promising step towards sustainable urban development, demonstrating the potential of vertical facades in contributing to renewable energy goals while enhancing the urban landscape.